2007
DOI: 10.1029/2006jd007217
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of aircraft engine soot particles under plume conditions: Effect of sulfuric and nitric acid processing

Abstract: [1] Hydration properties of original engine soot produced by burning TC1 aviation kerosene in aircraft engine combustor are studied under simulated plume conditions. Engine-generated soot demonstrates a high level of water uptake due to the existence of fraction of impurities originating within an engine. It contains 13.5 wt% water soluble compounds including 3.5 wt% organic and inorganic sulfates. Total amount of water vapor absorbed by engine soot particles increases with the temperature decrease in the exha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Among the N gases, HNO 3 is a condensable gas under conditions of very low plume temperatures (<200 K) and when the humidity is low so that water-ice does not yet form (Meilinger et al, 2005) In addition, some HNO 3 may be taken-up by H 2 SO 4 /H 2 O aerosols (Kä rcher, 1996;Romakkaniemi et al, 2004) and by contrail particles at high relative humidity and at temperatures below 222 K (Gleitsmann and Zellner, 1999). Shonija et al (2007) have also argued that HNO 3 may contribute to the activation of soot particles, which is usually considered to be mediated by H 2 SO 4 . Measurements in cirrus clouds indicate uptake of several percent of the HNO 3 by ice clouds depending on ambient temperature (Voigt et al, 2006(Voigt et al, , 2007.…”
Section: Nitrogen Containing Speciesmentioning
confidence: 99%
“…Among the N gases, HNO 3 is a condensable gas under conditions of very low plume temperatures (<200 K) and when the humidity is low so that water-ice does not yet form (Meilinger et al, 2005) In addition, some HNO 3 may be taken-up by H 2 SO 4 /H 2 O aerosols (Kä rcher, 1996;Romakkaniemi et al, 2004) and by contrail particles at high relative humidity and at temperatures below 222 K (Gleitsmann and Zellner, 1999). Shonija et al (2007) have also argued that HNO 3 may contribute to the activation of soot particles, which is usually considered to be mediated by H 2 SO 4 . Measurements in cirrus clouds indicate uptake of several percent of the HNO 3 by ice clouds depending on ambient temperature (Voigt et al, 2006(Voigt et al, , 2007.…”
Section: Nitrogen Containing Speciesmentioning
confidence: 99%
“…Ferry et al, 2002, Lammel andNovakov, 1995;Pöschl, 2002) as well as the ability of soot to act as cloud condensation nuclei (Decesari et al, 2002;Persiantseva et al, 2004;Petzold et al, 2005;Perraudin et al, 2007;Shonija et al, 2007). The ability of soot PM to condense water also strongly influences its atmospheric lifetime.…”
Section: Trace Gas Uptake On Soot Surfacesmentioning
confidence: 99%
“…The results obtained for the freezing of 4 ML of water are surprising since we found that water remains liquid/ amorphous and didn't form crystalline ice, even at low temperature (215 K). However, supercooled water has already been observed in porous systems, 38 but the pore volume of AEC soot is low, 35 even lower than that of commercial and laboratory made samples. This low porosity can be explained by a high fraction of soluble and volatile components on the surface, which can fill or close the pores.…”
Section: Water Freezingmentioning
confidence: 99%
“…Investigation of the water adsorption on AEC soot at temperatures down to 233 K shows that the amount of adsorbed water at high RH increases as the temperature decreases. 35 We assume that 4 ML of water molecules do not form a bulk structure even at low temperature as no signature of the ice I h phase was measured by neutron diffraction. Diffractograms corresponding to the cooling of 4 ML of water adsorbed on AEC soot show a broad asymmetric peak at 1.86 A ˚À1 (noncrystalline structure), which is observed even at 215 K (Fig.…”
Section: Water Freezingmentioning
confidence: 99%